Joint effect of elevated-c-reactive protein level and hypertension on new-onset stroke: A nationwide prospective cohort study of CHARLS - Chen, Xuanli; Liu, Siyuan; Chu, Jiadong; Hu, Wei; Sun, Na; Shen, Yueping (Frontiers in Public Health, 2022)
Background and aims：This study aimed to examine the associations between the combination of elevated-C-reactive protein (CRP) level and hypertension increased the risk of stroke among the middle-aged and elderly Chinese. Methods: This nationwide prospective study included Chinese participants aged ≥ 45 years in the China Health and Retirement Longitudinal Study (CHARLS) recruitment in 2011. Data on CRP levels and hypertension were obtained (N=9821). Multivariable Cox proportional hazards regression models were used to estimating hazard ratios (HRs) with 95% confidence interval (95%CI) of new-onset stroke risk according to elevated-CRP level and hypertension. Moreover, the area under the curve (AUC), net reclassification index (NRI), and integrated discrimination improvement (IDI) were used to evaluate the incremental predictive value. Results: A total of 184 stroke events occurred during the 4-year follow-up period. Compared to the normal CRP levels (CRP ≤3 mg/L) and non-hypertension, the adjusted HRs and 95%CI were 1.86 (0.90–3.85) for individuals with elevated-CRP levels alone, 2.70 (1.71–4.28) for those with hypertension alone and 4.80 (2.83-8.12) for those with comorbid elevated-CRP levels and hypertension. People with the coexistence of elevated-CRP levels and hypertension had the highest risk of new-onset stroke among all subgroups analyses. Lastly, adding the combination of elevated-CRP levels and hypertension to conventional factors significantly improved the risk prediction for new-onset stroke. Conclusion: Our findings indicate that the combined effect of elevated-CRP levels and hypertension increase the risk of new-onset stroke among the middle-aged and geriatric Chinese population.